Architecture of Polish water sports facilities located in parks in the interwar period - Kocki, Wojciech (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
In the interwar period, many sports and recreation facilities were built in Poland. Some of them were located in unique spaces with significant aesthetic and environmental values. One of the examples of such facilities are open swimming pools in the city of Wisła, Ciechocinek and Lviv. Examples of these objects show thoughtful compositional and urban solutions. Such a location of the facilities surrounded by nature was conducive to rest and practicing sports undisturbed by city noise. The location of water sports facilities in parks had many advantages which resulted in better conditions for practicing sports.